Neurobehavioral toxicity. - Walker, B. (National Medical Association, 2000)
A growing number of agents are known to perturb one or more of the interconnected processes of the central nervous system. At the same time, there is an increase in the incidence of neurobehavioral disorders that are confronting clinicians with baffling symptoms and presentations that seem uncommon. Fundamental to the assessment of the environmental-relatedness of the syndromes is a work and exposure history, including information different from that routinely obtained in the clinical setting. Exposure examples are described to suggest the scope of inquiry necessary to differentiate neurotoxic syndromes from nonneurotoxic illness.